2017
DOI: 10.1016/j.jiph.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter antibiotics in Saudi Arabia, an urgent call for policy makers

Abstract: Antibiotics over-consumption is a pandemic that has a tremendous cost on the overwhelmed healthcare system. The accessibility of antibiotics coupled with the misconception of public toward those drugs both of which implicated in the use and misuse of antibiotics. The aim of this study was to investigate the perception of the community toward antibiotics, its purpose and harmfulness, in addition to the accessibility of those drugs as over the counter and without prescriptions. We also investigated the behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 23 publications
3
50
0
1
Order By: Relevance
“…Medicines intended for self-medication are called over-the-counter medicines and are available without a medical prescription. In Saudi Arabia, for example, the accessibility of antibiotics over-the-counter (OTC) without prescriptions is an important factor that contributes to the public’s behaviour in respect of self-medicating [ 5 ]. Findings from a study conducted in 2010 in Riyadh, Saudi Arabia, showed that antibiotics could readily be obtained without a prescription in 244 (78%) of 327 pharmacies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicines intended for self-medication are called over-the-counter medicines and are available without a medical prescription. In Saudi Arabia, for example, the accessibility of antibiotics over-the-counter (OTC) without prescriptions is an important factor that contributes to the public’s behaviour in respect of self-medicating [ 5 ]. Findings from a study conducted in 2010 in Riyadh, Saudi Arabia, showed that antibiotics could readily be obtained without a prescription in 244 (78%) of 327 pharmacies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding knowledge questions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), a score of 1 was given to right answer which is the first choice for all questions except number 36 the right answer is the second choice. The total score was computed by summation of scores and it was 18, the range was (0-18).…”
Section: Methodology:-mentioning
confidence: 99%
“…Terdapat sebuah penelitian yang menghitung jumlah apotek di Surabaya yang melayani pembelian antibiotik tanpa resep dokter. 24 10,25 Hasil penelitian yang dilakukan di Surabaya dan diperkuat dengan bukti-bukti terpublikasi tersebut menegaskan besarnya penggunaan antibiotik tanpa resep dokter oleh populasi pada rentang usia produktif. Salah satu pertimbangan kelompok usia produktif dalam menggunakan antibiotik tanpa resep dokter adalah efektivitas biaya.…”
Section: Pembahasanunclassified